Zhou Yu's train [videorecording (DVD)] = Zhou Yu de huo che - Gong, Li, 1965-; Liang, Jiahui; Sun, Honglei; Sun, Zhou; Beicun, 1965- (Columbia TriStar Home Entertainment, 2004)
"Twice a week, Zhou Yu, a beautiful artisan, takes the train to faraway Chongyang, where she indulges in a torrid affair with Chen Ching, her poet-lover. United by their passion, he finds in Zhou the ultimate muse, while she believes Chen to be her ideal soul mate. But accompanying Zhou on her lonely train rides are two individuals who threaten to derail her romantic idyll: Zhang Qiang, a young doctor hopelessly obsessed with her, and Xiu, a mysterious young woman who bares a striking resemblance to Zhou and seems to be following her every move"--Container.